المعنى الظاهر والمعنى الباطن عند الحسين الذهبي في التفسير والمفسورن - Muhammad Farid Abdullah (IAIN Salatiga, 2017)
This is a mini research by using literature review to examine the extent of the thought concept about dzahir and bathin meaning by Husain al Dzahabi and other interpreters and then analyzed by linguistics-semantics. Based on the study, the author concludes that: first, the dialogue of thought about dhahir and bathin meaning has produced various characteristics of Qur'anic interpretation as dynamic and meaningful text. Second, dzahir meaning has a clearer character, and is considered stronger as hujjah, but the bathin meaning can also be accepted scientifically if it is supported by the right dalil or qarinah. Third, both in aqli and naqli, the existence of dzahir and bathin meaning is justified. Fourth, the Qur'anic discourse is the more suitable approach in line with the rules of Qur’anic understanding and the standard of interpretation in Islam.